المنهج الصــوتي-الخـطـي في تعليم اللغة العربية وتعلّها في الطّور الأول من التعليم الابتدائي. - بوحملة, عمر (جامعة الوادي - University of Eloued, 2022)
ملخص: يهدف المقال الموسوم: "المنهج الصّــوتي-الخـطـي في تعليم اللّغة العربيّة وتعلّها في الطّور الأوّل من التّعليم الابتدائي" إلى الإجابة عن سؤاليّن مهميّن الأوّل: ما الإجراءات العمليّة الّتي يتعـيـّن عـلى أساتذة الطّور الأول، تنفيذهـا داخـل حجرة الدّرس، بهدف تحسين مستوى المتعلّمين فـي ميدان فهم المكتوب، والارتقاء بكفاءات التّلاميذ؟ والثّاني : ما مهارات الوعي الصّوتي الّتي يجب اكسابها للمتعلّمين في هذا الطّور ؟ وللإجابة عن السّؤالين المطروحين تمّ تحليل منهاج اللّغة العربية للطور الأول (السّنة أولى والثّانية ابتدائي )للبحث عن المعارف الأساسية الّتي يجب أن يمتلكها الأستاذ لتطبيق المنهج الصوتي –الخطي ،وتوضيحها بالعودة إلى كلّ من اللّسانيات وعلم الأصوات ، وتفحص كتاب القراءة والأنشطة اللّغوية للسّنتين لتحديد مهارات الوعي الصّوتي المقرر اكسابها للمتعلّمين وشرح طريقة تقديمها عمليّا Abstract : The article entitled " The phonetic-linear method in teaching and learning Arabic in the first phase of primary education aims answer two important questions. First, what are the practical procedures that first-year teachers should implement in the classroom, with the aim of improving the level of learners in the field of understanding the written, and developing students’ competencies? Second, what are the phonemic sensitization skills that must be acquired for learners at this stage? In order to answer the two questions posed, the Arabic language curriculum for the first phase (first and second years of primary school) was analysed to search for the basic knowledge that the teacher must possess to apply the phonetic-linear curriculum. We aim to clarify this with reference to both linguistics and phonology, and review the two-year language reading and activity book to determine what phonemic awareness skills learners need to acquire and how to present them in practice
مقال
Keywords: القراءة المقطعية؛ المنهج الصّوتي-الخطي؛ الوعي الصّوتي؛ مهارات الوعي الصّوتي; syllabic reading; phonetic-linear method; phonological awareness; Phonological awareness skills.